Konteks Tuturan dalam Cerita Anak Durhaka Ojuang yang terdapat di Kabupaten Kuantan Singingi Riau - Musliha Wardana; Khalidatun Nuzula; Mita Domi Fella Henanggil; Sri Antoni (CV Berkah Syahdin Trust, 2025)
This study is motivated by the importance of examining folklore as intangible cultural heritage, particularly the legend of